DASAR PENGEMBANGAN KURIKULUM PENDIDIKAN AGAMA ISLAM - Sitika, Achmad Junaedi; Amal, Nailah Syahidah; Fadhilah, Nusha; Rahmawati, Rif’ah Fitri (Universitas Muhammadiyah Tapanuli Selatan, 2025)
The development of the Islamic Religious Education (IRE) curriculum refers to the fundamen-tal principles found in the Qur'an and Sunnah. This study employs a literature review method, drawing from books, journal articles—both national and international—as well as other rele-vant literature. It also examines the implementation of the curriculum in various Islamic edu-cational institutions. The findings indicate that integrating the values of the Qur'an and Sunnah into the development of the IRE curriculum fosters a holistic educational approach, balancing character formation, understanding of the Qur'an and Sunnah, the philosophy and objectives of Islamic education, social foundations, and cultural foundations. A curriculum based on these two primary sources not only strengthens students’ Islamic identity but also prepares them to face global social dynamics while upholding moral and ethical values. These findings suggest that developing the IRE curriculum based on the Qur'an and Sunnah is an effective strategy for nurturing a generation that is faithful, knowledgeable, and adaptable to the changes of the times.